Hypothyroidism and Levothyroxine, Review Article - Waseem Akhtar, Fayaz Ahmad Moghal, Muhammad Ishaq, Alliya Naseem, Azhar Hussain Rana, Hamid Nadeem, Muhammad Naseem ul Huda, Khalid Mahmoud El Barki, Shehla Naseem, Muhammad Zaman Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Hypothyroidism is a communal thyroid hormone deficit disorder. It affects ten percent of the general population and it is estimated that 5% go undiagnosed. If not treated properly, it can cause serious health problems and even death1-2. There is no great variability in the clinical picture or specificity of symptoms, therefore it is most often diagnosed mainly biochemically3. Levothyroxine (L-thyroxine, LT4) is the gold standard in the treatment of hypothyroidism. It was introduced in 1949 and has since improved the lives of millions of hypothyroid patients. As it is usually given for the patient's life, the dose can be affected by physiological changes. In addition, the dosage should be adjusted in the event of concomitant medical conditions, pregnancy and the elderly. Clinically significant interactions between levothyroxine and other drugs, food and dietary supplements may occur. This can change the safety and effectiveness of the treatment4-5. The physician should be aware of the use of thyroxine and its interactions with other medications and diet6. Hypothyroidism, levothyroxine uses and dose adjustments and their interactions will be discussed in this review.